Is information and communication technology (ICT) the right strategy for growth in Mexico? - Francisco Caudillo Sanchez (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
Although empirical evidence available suggests that information and communication technologies (ICT) have positively contributed to important sectors of the Mexican economy, it is still unknown to which extent ICT have truly contributed to productivity among these sectors. The increasing implementation and imports of ICT technologies, the growing demand for ICT-skilled human capital and training, the rising level of wages and the large demand and adoption of these technologies seem to indicate a positive correlation between ICT implementation and economic growth in Mexico. To answer whether ICT may be a key strategy for economic growth in the Mexican economy is the main purpose of this work.
Keywords: D24; D83; F43; J24; J31; O33; 330; Information technology; total factor productivity; growth; knowledge; human capital; technology diffusion